The Representation of Multicultural Education in Film “Raya and The Last Dragon” - Muflikhah Ulya; Muhammad Altaf Rezaian (Proceedings Series on Physical & Formal Sciences, 2022)
The film is one of the media that represents the multicultural concept. Representation in films can create a paradigm that indirectly influences the audience's mindset. Among various genres of film, film animation is one genre that can attract the attention of various levels of society of all ages. Animated films are easier to accept because they have a weak storyline and are full of moral messages. One of the public's animated films in great demand is "Raya and The Last Dragon." This film tells the story of life in a fantasy land called Kandra. A land where people from different tribes can live in harmony with guardian dragons. Therefore, this research was conducted to know what forms of representation of multiculturalism in the film "Raya and The Last Dragon." This research was conducted using the descriptive qualitative method. While the theory used in this study is the semiotic theory of John Fiske: the level of reality, representation, and ideology. The result of this research is discovering a form of representation of multiculturalism which is the basis of multicultural education.